2019
DOI: 10.1002/jbm.a.36833
|View full text |Cite
|
Sign up to set email alerts
|

Local application of alendronate controls bone formation and β‐tricalcium phosphate resorption induced by recombinant human bone morphogenetic protein‐2

Abstract: This study examined the ability of local alendronate (ALN) administration to control β-tricalcium phosphate (β-TCP) resorption as well as the induction of bone formation by recombinant human bone morphogenetic protein-2 (rhBMP-2). A 15-mm criticalsized bone defect was created in the diaphysis of rabbit ulnae. Nine female rabbits (4 to 5 months-old) were divided into 3 groups. Group 1 (n = 6 ulnae) animals received implants consisting of β-TCP granules and 25 μg of rhBMP-2 in 6.5% collagen gel.Group 2 (6 ulnae)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 66 publications
(121 reference statements)
1
10
0
Order By: Relevance
“…Several researchers have developed scaffolds able to reproduce the physical and mechanical nature of autologous tissue and to promote osteoconduction in bone regeneration. Different materials have been already proposed in scaffolds [40]. The principal goal is to reduce cost and hospitalization time in patients that require bone regeneration treatments [41].…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Several researchers have developed scaffolds able to reproduce the physical and mechanical nature of autologous tissue and to promote osteoconduction in bone regeneration. Different materials have been already proposed in scaffolds [40]. The principal goal is to reduce cost and hospitalization time in patients that require bone regeneration treatments [41].…”
Section: Bone Regenerationmentioning
confidence: 99%
“…Delivering distinct GFs simultaneously, overall, enhances the innate bone-healing process [ 43 ]. Local alendronate administration to control β-tricalcium phosphate (β-TCP) resorption and the induction of bone formation by rhBMP-2 were attempted [ 44 ]. However, the administration of rhBMP-2 promoted a burst release and reduced osteoclastic resorption of β-TCP induced by rhBMP-2, resulting in decreased bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…β-TCP is gradually degraded during bone remodeling and is finally replaced by mature new bone. We have previously shown that the main resorption process of β-TCP is via osteoclasts [28][29][30][31][32][33][34], and the macropore and micropore structures within β-TCP affect not only material resorption but also bone formation [35][36][37]. We found that a combination of β-TCP with a superior microstructure and local BMP-2 administration accelerates bone reconstruction.…”
Section: Introductionmentioning
confidence: 99%